Timed artificial insemination in yearling beef heifers: 7-11 Cosynch VS. Cosynch - A.W. Thompson; C.D. Holladay; D.R. Eborn; David M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2003)
Previous research demonstrated that an estrus-synchronization program using a short period of melengestrol acetate (MGA) feeding in conjunction with a Cosynch protocol was effective in synchronizing estrus in postpartum beef cows. The objective of our study was to test this synchronization protocol (7-11 Cosynch) in yearling beef heifers in comparison to a Cosynch protocol. Fifty-eight commercial beef replacement heifers were assigned randomly to two protocols: Cosynch (n=29) and 7-11 Cosynch (n=29). Beginning on day 1, heifers in the 7-11 Cosynch protocol were fed MGA (0.5 mg/heifer daily) for 7 days. On day 7, the last day of MGA feeding, the heifers on the 7-11 Cosynch protocol received an injection of PGF2α. On day 11 all 58 heifers received an injection of GnRH (100 Î¼g). On day 18, all 58 heifers were injected with PGF2α. On day 20, all of the heifers received a 100 Î¼g dose of GnRH by injection and were artificially inseminated. Ultrasonography was used to determine pregnancy status 29 days after breeding. A greater percentage (P<0.01) of heifers were pregnant after the 7-11 Cosynch treatment (67%) than after the Cosynch treatment (31%). This study demonstrates the potential of achieving acceptable pregnancy rates using timed artificial insemination in yearling beef heifers.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Timed Timed artificial insemination; 7-11 Cosynch VS. Cosynch; Yearling heifers